A new method for mixing of suspended superparamagnetic beads using variable electromagnetic fields. Issue 7 (21st July 2015) - Stange, Robert; Lenk, Felix; Eckert, Kerstin; Lenk, Stephan; Bley, Thomas; Boschke, Elke
<x xml:space="preserve">Abstract</x> The detection, identification, and analysis of bacterial pathogens are highly important for identifying potential health risks. Often, the first step of the process is an enrichment of the pathogens to such densities that exceed the detection limits of analytical instruments. In this context, biomagnetic separation is a promising approach to achieve this enrichment due to its selectivity and efficiency. Here, we present the electromagnetic sample mixer (ESM), an innovative device that may optimize this process. The aim of the ESM is to improve the binding between the superparamagnetic particles (beads) and the intended biological targets through the movement of the beads using variable magnetic fields to reduce these costly beads and save process time. The magnetic fields are generated using three electromagnets equipped with magnetic cores with special pole shoe geometry. This geometry was improved by numerical simulation of the magnetic field using FEMLAB 3. Also, proof‐of‐principle studies with Escherichia coli were performed by comparing the separation efficiencies received using the ESM and the conventional Dynabeads MX4 Mixer (Life Technologies AG, Carlsbad, CA, USA). The results show a similar performance of these two devices.